Prospects for Development of Direct International Investment - O. M. Motuzka (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Reforms in management of international investment and outlining the investment prospects are of primary importance for creating and sustaining the investment friendly environment and opening up wider opportunities for achieving the goals related with financing of development. Direct international investment has had highly positive tendency. International investment flows began to grow rapidly in 2013. Although this trend can be found mainly in developed countries, experts argue that investment inflow in developing and transitional economies, reaching the historic maximum in 2013 in spite of uncertainties in the economic and political situation, is expected to be reasonably high in the forthcoming years. As regards investment policies of countries, they are focused, as before, on liberalization and attraction of investment. Some countries tend to pursue the policy of privatization, in infrastructure sectors in particular. Others could improve the procedures for business operation, create special economic zones or introduce investment preferences in other forms. Another remarkable feature is enforcement or revisions (in view of the current conditions or needs of individual countries) of legal framework for investment, mainly in developing countries, such as African ones. The current investment policies across the globe feature a certain kind of duality: measures to deepen liberalization of investment activities and attract investment are taken in parallel with ones to reinforce the regulatory regime of investment for purposes of domestic policy implementation. The central objective of investment policy is to make investment serve the benefit of sustained development, given the maximal utilization of its advantages and mitigation of negative effects.